Perlindungan Hukum Keselamatan Penumpang Transportasi Laut Berdasarkan Undang-Undang No. 17 Tahun 2008 tentang Pelayaran (SETARA : Jurnal Ilmu Hukum, 2022)
This article examines the legal protection of sea transportation passengers under Law Number 17 of 2008 on Shipping. The topic is important because Indonesia's maritime geography makes sea transport a crucial public service, while recurring maritime accidents continue to reveal weaknesses in passenger safety systems, supervision, and operational compliance. Using normative juridical research with statutory and conceptual approaches, the article analyzes the legal duties of shipping companies, the role of government supervision, and the framework of liability for harm suffered by passengers. The study finds that the Shipping Law has provided a clear basis for carrier responsibility and passenger safety, but implementation remains uneven because safety standards, human resources, technology, and enforcement mechanisms do not always operate effectively. The article argues that stronger supervision, clearer accountability, and continuous regulatory refinement are needed so that legal protection for sea passengers is not merely declaratory but genuinely effective in practice.
Keywords: Passenger Safety; Sea Transportation; Shipping Law; Carrier Liability; Legal Protection